G113(P) Innovative quality improvement project to improve oral health knowledge and practices of children with diabetes. (25th October 2020) - Woon Sam, K; Uppal, S; Utting, C; Aswani, N; Dickenson, A; Okike, I
Abstract : Aims: Patients with diabetes are at a higher risk of developing a number of oral health (OH) conditions, most notably periodontal disease. This project sets out to assess and increase patient knowledge about OH in a paediatric diabetic outpatient clinic. Methods: Using a Plan-Do-Study-Act (PDSA) methodology, children being seen for diabetic outpatient review were given the opportunity to see a dentist in addition to their regular team. Families who accepted this offer were given oral health education, toothbrushing instruction and advice about how to tackle risks specific to them. For each patient seen between September and October 2019, the dentist completed an oral health recording tool (OHRT). This provided the opportunity to study the patient's current practices and knowledge about diabetes and OH. In future reviews, the OHRT will be repeated to assess improvement in patient's knowledge following our intervention. This is a Trust approved quality improvement project. Results: The results of the completed pre-intervention OHRTs are presented here. Out of the 28 children seen, 89% visit a dentist regularly. However, most of the families (61%) had no knowledge that diabetes had any impact on oral health and just 7% were aware of the specific risks to gingival health. 57% were unaware of risk reducing strategies and 14% were brushing their teeth less than once a day. Conclusion: This project aligns with the Making Every Contact Count initiative and is the first of its kind to our knowledge. The majority of families from our initial cohort lacked awareness about the risks of diabetes to OH and about different preventative strategies, justifying the need for further education in this high risk patient group. We have demonstrated that giving this preventive advice is possible without the need for additional appointments for children with diabetes. In addition, undergraduate dental students are now part of the OH education team thereby increasing the number of patients that can be seen on any one clinic and expanding the students' clinical experience.